Rapunzel syndrome in a 3-year-old boy: A menace too early to present - Mritunjay Kumar; Madhukar Maletha; Sakshi Bhuddi; Rashmi Kumari (Wolters Kluwer Medknow Publications, 2020)
Rapunzel syndrome is a rare type of trichobezoar with an extension of the hair into the small bowel. Clinical presentation is deceptive and vague, ranging from asymptomatic abdominal mass to gastrointestinal perforation. There are only few cases reported in literature, with the youngest age being 3 years. We present the case of a 3-year-old male child presenting with Rapunzel syndrome and features of subacute intestinal obstruction.